IDENTITAS ARSITEKTUR MANDAR PADA BANGUNAN DI KELURAHAN BANGGAE KABUPATEN MAJENE - Nurmiati Zamad (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2017)
The results of this study indicate that the typical roof shape ornament Mandar in terms of physical form of the use of roof teppang (Butung-Butung) most are still used with value (± 52%). Ornaments are very significant symbolic meaning why the identity architecture still used on building Mandar ethnic year 1960-2016, especially in buildings Mandar contemporary architecture, and in terms of nonphysical factors are influenced by social status and environmental factors.